PERKEMBANGAN ASAS TUGAS PEMBANTUAN DI INDONESIA - Rauf, Rahyunir (UIR PRESS, 2018)
In the long journey of development of a government increasingly multiply and enrich the understanding of the government itself, so that the concepts of government can be viewed from various angles and aspects that can further clarify the notion of the concept of government itself, one of which is the concept of the principle of governance. The existence of a Local Government in the system of government is an integral part of a system of state government or national government, even the concept and theoretical existence of local government is much earlier than the existence of elements of central government or state government. The principle of